The Benefits and Challenges of Employment for Working Professionals Diagnosed with Mental Illness. - Elliott, Marta; Reuter, Jordan C. (Community Mental Health Journal, 2022)
The purpose of this study is to explore how professional employment impacts mental health among people with mental illness, and how having a mental illness impacts job performance, both positively and negatively. The research is based on in-depth interview data from 56 professionals diagnosed with mental illness, and the interview transcripts are analyzed in accordance with the flexible coding model of qualitative data analysis. We find that working conditions of professional jobs pose challenges to managing symptoms of mental illness, including the pressures of responsibility and exposure to secondary trauma. However, professional employment also provides benefits such as social connections and feeling accountable. Similarly, symptoms cause problems at work like having angry outbursts, yet experience with mental illness informs job performance such as by increasing empathy with others. We use these findings to recommend new directions for research and argue for inclusion of people with mental illness in the workplace.